Environmentally friendly bamboo-wood composite material and preparation method thereof
Through N/S doped TiO2 nanopowder, tanninic acid and silane coupling agent modification and enzyme treatment, combined with sonication and tung oil coating, the problems of harmful and insufficient glue strength of existing bamboo and wood composite glue are solved. Prepare environmentally friendly bamboo and wood composite materials with environmental protection, antibacterial, mildew-proof, high durability and high glue strength.
Patent Information
- Application Number
- CN202411356631.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The glue agents used in the preparation of existing bamboo and wood composite materials often contain formaldehyde or volatile organic solvents, which leads to the material produced being harmful to the human body and the glue strength is insufficient, which limits its application.
Modified nanopowder with N/S doped TiO2 nanopowder, tanninic acid and silane coupling agent, combined with enzyme treatment and ultrasonic treatment, modified aqueous acrylic resin adhesive is prepared, reducing the amount of adhesive used, and improving the bonding strength. And enhance waterproof and moisture resistance through tung oil surface coating.
The environmentally friendly bamboo and wood composite material produced has low formaldehyde release, antibacterial, anti-mold, anti-viral, good durability, high glue strength, excellent mechanical properties, low cost, and waterproof, moisture resistance, wear resistance, flame retardant and other effects.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of bamboo-wood composite materials, and in particular to an environmentally friendly bamboo-wood composite material and a preparation method thereof. Background Art
[0002] Nowadays, people's living standards are getting higher and higher. Housing is a rigid demand of people. Everyone has this demand. However, when decorating a house, more and more chemicals are used. These chemicals will emit a series of chemical elements during use. Some of these elements are pollution-free. But some are highly polluting. Therefore, people begin to pay attention to environmental protection and the use of environmentally friendly products. Bamboo, wood and hemp and other products are natural products. They have no radiation and will not emit polluting elements. They are environmentally friendly products and can also make people feel close to nature. Products made of these raw materials are used in many places, such as curtains, floors or beds and chairs.
[0003] However, in the existing process of preparing bamboo-wood composite materials, bamboo powder and wood powder are usually mixed, and after adding adhesive and mixing evenly, hot pressing is formed into a composite board. The adhesive often releases formaldehyde or volatile organic solvents (VOCs), which makes the prepared bamboo-wood composite material harmful to the human body and limits its application.
[0004] Chinese invention patent CN118493546B discloses a lightweight bamboo-wood composite material and its preparation method, which belongs to the technical field of bamboo-wood composite materials. N-doped TiO2 / SiO2 hollow nanospheres are prepared, nano-scale elemental silver is deposited on the surface in situ, Cu oxide is fixed, modified by tannic acid and silane coupling agent, polymerized with acrylic monomer to obtain modified acrylic resin adhesive, added with wood powder and bamboo powder, microwave treated, hot pressed, coated with tung oil, and dried to obtain a lightweight bamboo-wood composite material. However, the obtained bamboo-wood composite material does not have good bonding strength.
[0005] Therefore, it is necessary to develop a method in which the production process is environmentally friendly and the obtained product bamboo-wood composite material does not release formaldehyde. Summary of the invention
[0006] The purpose of the present invention is to provide an environmentally friendly bamboo-wood composite material and a preparation method thereof. The amount of adhesive added is low, and pollutants such as formaldehyde in the environment can be degraded to a certain extent. It has environmental protection, antibacterial, anti-mildew and anti-viral activities, good durability, high bonding strength, good mechanical properties, low cost, and has the effects of waterproof, moisture-resistant, wear-resistant, flame-retardant, etc., and has broad application prospects.
[0007] The technical solution of the present invention is achieved in this way:
[0008] The present invention provides a method for preparing an environmentally friendly bamboo-wood composite material, comprising the following steps:
[0009] S1. Preparation of N / S-doped TiO2 nanopowder: Tetrabutyl titanate and thiourea were dissolved in ethanol, water was added dropwise, stirred for reaction, centrifuged, washed, dried, and calcined to obtain N / S-doped TiO2 nanopowder;
[0010] S2. Preparation of tannic acid-modified nanopowder: The N / S-doped TiO2 nanopowder obtained in step S1 was added to water, tannic acid and Tris-HCl buffer were added, the pH value of the solution was adjusted, the reaction was heated and stirred, centrifuged, washed, and dried to obtain tannic acid-modified nanopowder;
[0011] S3. Preparation of modified nanopowder: The tannic acid-modified nanopowder obtained in step S2 was added to water, a silane coupling agent was added, the reaction was heated and stirred, centrifuged, washed, and dried to obtain a modified nanopowder;
[0012] S4 modified water-based acrylic resin adhesive preparation: the modified nanopowder obtained in step S3 was added to water, an acrylic monomer was added, under inert gas protection, an initiator system was added, the reaction was heated and stirred, and part of the solvent was removed under reduced pressure to obtain a modified water-based acrylic resin adhesive;
[0013] S5. Enzyme treatment: Mix wood powder and bamboo powder and add to water, add complex enzyme, enzymolysis, enzyme inactivation, filtration, washing, drying, to obtain an enzyme-treated mixed powder;
[0014] S6 environmentally friendly bamboo composite material preparation: the enzyme treatment of step S5 prepared by adding the modified waterborne acrylic resin adhesive prepared in step S4, mixed, ultrasonic treatment, hot pressing, drying, to obtain a bamboo composite material;
[0015] S7. Preparation of environmentally friendly bamboo-wood composite material: coating the surface of the bamboo-wood composite material obtained in step S6 with a layer of tung oil and drying it to obtain an environmentally friendly bamboo-wood composite material.
[0016] As a further improvement of the present invention, the mass ratio of tetrabutyl titanate, thiourea, ethanol and water in step S1 is 15-22:1-2:120-150:7-10, the stirring reaction time is 0.5-1h, the calcination temperature is 500-700°C, and the time is 2-4h.
[0017] As a further improvement of the present invention, the mass ratio of the N / S-doped TiO2 nanopowder, tannic acid and Tris-HCl buffer in step S2 is 15-20:5-7:10-12, the Tris-HCl buffer is 1.5-2.5 mol / L Tris-HCl buffer, the amount of Tris-HCl buffer added is such that the pH value of the system is 8.5-8.8, the temperature of the heating and stirring reaction is 40-50°C, and the time is 1-3h.
[0018] As a further improvement of the present invention, the mass ratio of the tannic acid modified nanopowder and the silane coupling agent in step S3 is 17-22:3-5, the silane coupling agent is a mixture of KH550 and KH570, the mass ratio is 2-4:7-10, the temperature of the heating and stirring reaction is 45-55°C, and the time is 1-3h.
[0019] As a further improvement of the present invention, the mass ratio of the modified nanopowder and the acrylic monomer in step S4 is 3-5:30-35, the acrylic monomer includes methacrylic acid, 2-hydroxyethyl acrylate, N-hydroxymethyl acrylamide, and methyl acrylate, and the mass ratio is 12-15:7-10:3-5:2-3, the initiator system includes an initiator and a co-initiator, and the mass ratio is 4-6:1, the initiator is at least one of sodium persulfate, potassium persulfate, and ammonium persulfate, and the co-initiator is sodium sulfite. The amount of the initiator system added is 0.5-1wt% of the total mass of the system, the temperature of the heating and stirring reaction is 55-65°C, the time is 3-5h, and the relative density of the modified water-based acrylic resin adhesive is 1.1-1.15.
[0020] As a further improvement of the present invention, the composite enzyme in step S5 includes hemicellulase and laccase in a mass ratio of 2-4:7-9, the mass ratio of the wood powder, bamboo powder and composite enzyme is 55-60:120-150:2-4, the enzymatic hydrolysis temperature is 50-60°C, and the time is 0.5-1h.
[0021] As a further improvement of the present invention, the mass ratio of the enzyme-treated mixed powder and the modified water-based acrylic resin adhesive in step S6 is 10-15:8-10, the temperature of the hot pressing molding is 145-155°C, the pressure is 5.5-7Mpa, the time is 10-20min, the power of the ultrasonic treatment is 700-1000W, and the time is 10-15min; the coating amount of the tung oil in step S7 is 0.03-0.05g / cm 2 .
[0022] As a further improvement of the present invention, the present invention specifically comprises the following steps:
[0023] S1. Preparation of N / S doped TiO2 nanopowder: 15-22 parts by weight of tetrabutyl titanate and 1-2 parts by weight of thiourea are dissolved in 120-150 parts by weight of ethanol, 7-10 parts by weight of water are added dropwise, the reaction is stirred for 0.5-1h, centrifuged, washed, dried, and calcined at 500-700°C for 2-4h to obtain N / S doped TiO2 nanopowder;
[0024] S2. Preparation of tannic acid modified nanopowder: 15-20 parts by weight of the N / S doped TiO2 nanopowder obtained in step S1 was added to 200 parts by weight of water, 5-7 parts by weight of tannic acid and 10-12 parts by weight of 1.5-2.5 mol / L Tris-HCl buffer were added, the pH value of the solution was adjusted to 8.5-8.8, heated to 40-50 ° C, stirred for 1-3h, centrifuged, washed, and dried to obtain tannic acid modified nanopowder;
[0025] S3. Preparation of modified nanopowder: 17-22 parts by weight of the tannic acid modified nanopowder obtained in step S2 was added to 200 parts by weight of water, 3-5 parts by weight of a silane coupling agent was added, heated to 45-55 ° C, stirred for 1-3h, centrifuged, washed, and dried to obtain a modified nanopowder;
[0026] The silane coupling agent is a mixture of KH550 and KH570, with a mass ratio of 2-4:7-10;
[0027] S4. Preparation of a modified waterborne acrylic resin adhesive: 3-5 parts by weight of the modified nanopowder obtained in step S3 was added to 150 parts by weight of water, 30-35 parts by weight of an acrylic monomer was added, under inert gas protection, an initiator system was added, heated to 55-65 ° C, the reaction was stirred for 3-5h, and part of the solvent was removed under reduced pressure to obtain a modified waterborne acrylic resin adhesive having a relative density of 1.1-1.15;
[0028] The acrylic acid monomers include methacrylic acid, 2-hydroxyethyl acrylate, N-hydroxymethyl acrylamide, and methyl acrylate in a mass ratio of 12-15:7-10:3-5:2-3;
[0029] The initiation system comprises an initiator and sodium sulfite in a mass ratio of 4-6:1;
[0030] S5 enzyme treatment: 55-60 parts by weight of wood flour and 120-150 parts by weight of bamboo powder were mixed and added to 500 parts by weight of water, 2-4 parts by weight of complex enzyme was added, enzymatic hydrolysis was carried out at 50-60 ℃ for 0.5-1h, the enzyme was inactivated, filtered, washed and dried to obtain an enzyme-treated mixed powder;
[0031] The complex enzyme includes hemicellulase and laccase in a mass ratio of 2-4:7-9;
[0032] S6. Preparation of environmentally friendly bamboo composite materials: 8-10 parts by weight of the modified waterborne acrylic resin adhesive prepared in step S4 was added to 10-15 parts by weight of the enzyme-treated mixed powder prepared in step S5, mixed evenly, ultrasonically treated at a power of 700-1000W for 10-15min, hot-pressed at a temperature of 145-155°C, a pressure of 5.5-7Mpa, for 10-20min, and dried to obtain a bamboo composite material;
[0033] S7. Preparation of environmentally friendly bamboo-wood composite material: The surface of the bamboo-wood composite material obtained in step S6 is coated with a layer of tung oil, the coating amount being 0.03-0.05g / cm 2 , dried to obtain an environmentally friendly bamboo-wood composite material.
[0034] The present invention further protects an environmentally friendly bamboo-wood composite material prepared by the above preparation method.
[0035] The present invention has the following beneficial effects:
[0036] The present invention prepares a N / S doped TiO2 nano powder, wherein N doping can not only change the crystal structure of TiO2 and inhibit the recombination rate of photogenerated electrons and holes, but also enable TiO2 to utilize the visible light region, thereby greatly improving the photocatalytic activity of TiO2, and N doping can effectively reduce the energy required for generating photogenerated electron-hole pairs in TiO2, while S doping effectively reduces the recombination probability of photogenerated electrons and holes. Therefore, N- and S-doped TiO2 shows significant electronic conductivity, and due to the synergistic effect of different doped heteroatoms, the spectrum utilization range of TiO2 is broadened, the visible light region can be utilized, and the photocatalytic activity of TiO2 is greatly improved, so that the prepared composite material has better antibacterial, antiviral and anticorrosive properties, and improved durability, and at the same time, it can also catalyze and degrade formaldehyde, volatile organic matter, etc. in the air, thereby having better environmental protection performance.
[0037] N / S doped TiO2 nanopowder modified by tannic acid and silane coupling agent (KH550 and KH570), the amino group of coupling agent KH550 can form hydrogen bonds with the hydroxyl group of tannic acid to stabilize and fix it, and the double bond of KH570 can make the modified nanopowder copolymerize with acrylic monomer. At the same time, tannic acid can also form hydrogen bonds with O and N elements on the polyacrylic acid molecular chain, and can also form hydrogen bonds with hydroxyl and amino groups of cellulose in bamboo powder, so that the nanomaterial is evenly dispersed in the adhesive, and then evenly dispersed in the bamboo-wood composite material, which plays a good modification role, and also improves the bonding strength of the bamboo-wood composite material, reduces the amount of adhesive added, and at the same time, the mechanical properties are also greatly improved.
[0038] The present invention selects hemicellulase capable of degrading xylan and laccase capable of degrading lignin to perform enzymolysis treatment on bamboo powder, thereby forming active functional groups, achieving autogenous bonding, improving the bonding strength of the bamboo-wood composite material, reducing the amount of adhesive used, and improving environmental protection.
[0039] The invention mixes the enzyme-treated mixed powder with the modified water-based acrylic resin adhesive and then performs ultrasonic treatment to improve the roughness of the bamboo surface, increase the surface free energy of the bamboo surface, enhance the penetration of the adhesive, reduce the usage of the acrylic resin adhesive, and significantly improve the bonding strength of the bamboo-wood composite material.
[0040] Finally, a layer of tung oil is coated on the surface of the prepared bamboo-wood composite material. The main component of tung oil is α-tung oil triglyceride. After being coated on the surface of the bamboo-wood composite material, it can be cured into a film when reacting with oxygen in the air, thereby improving the composite material's waterproof, moisture-resistant, light-resistant, and anti-corrosion properties. After the tung oil that has penetrated into the bamboo-wood composite material is cured in situ, it can strengthen and enhance the wood cell wall, thereby improving the composite material's stability, hydrophobicity, wear resistance, and other properties, while further improving the flame retardant effect.
[0041] The amount of adhesive added to the environmentally friendly bamboo-wood composite material prepared by the present invention is relatively low, and it can degrade pollutants such as formaldehyde in the environment to a certain extent. It has environmental protection, antibacterial, anti-mildew and anti-viral activities, good durability, high bonding strength, good mechanical properties, low cost, and has the effects of waterproof, moisture-resistant, wear-resistant, flame-retardant, etc., and has broad application prospects. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Hemicellulase, 10,000 U / g, was purchased from Anhui Youtai Bioengineering Co., Ltd.; laccase, 50,000 U / g, was purchased from Shanghai Yuanye Biotechnology Co., Ltd.
[0044] Example 1
[0045] This embodiment provides a method for preparing an environmentally friendly bamboo-wood composite material, which specifically comprises the following steps:
[0046] S1. Preparation of N / S doped TiO2 nanopowder: 15 parts by weight of tetrabutyl titanate and 1 part by weight of thiourea were dissolved in 120 parts by weight of ethanol, 7 parts by weight of water were added dropwise, stirred for 0.5 h, centrifuged, washed, dried, and calcined at 500°C for 2 h to obtain N / S doped TiO2 nanopowder;
[0047] S2. Preparation of tannic acid-modified nanopowder: 15 parts by weight of the N / S-doped TiO2 nanopowder obtained in step S1 was added to 200 parts by weight of water, 5 parts by weight of tannic acid and 10 parts by weight of 1.5 mol / L Tris-HCl buffer were added, the pH value of the solution was adjusted to 8.5, heated to 40°C, stirred for 1h, centrifuged, washed, and dried to obtain tannic acid-modified nanopowder;
[0048] S3. Preparation of modified nanopowder: 17 parts by weight of the tannic acid-modified nanopowder obtained in step S2 was added to 200 parts by weight of water, 3 parts by weight of a silane coupling agent was added, heated to 45 ° C, stirred for 1h, centrifuged, washed, and dried to obtain a modified nanopowder;
[0049] The silane coupling agent is a mixture of KH550 and KH570, with a mass ratio of 2:7;
[0050] S4. Preparation of modified waterborne acrylic resin adhesive: 3 parts by weight of the modified nanopowder obtained in step S3 was added to 150 parts by weight of water, 30 parts by weight of acrylic acid monomer was added, under nitrogen protection, an initiator system was added, heated to 55 ° C, the reaction was stirred for 3h, and part of the solvent was removed under reduced pressure to obtain a modified waterborne acrylic resin adhesive having a relative density of 1.1;
[0051] The acrylic acid monomers include methacrylic acid, 2-hydroxyethyl acrylate, N-hydroxymethyl acrylamide, and methyl acrylate in a mass ratio of 12:7:3:2;
[0052] The initiation system includes sodium persulfate and sodium sulfite in a mass ratio of 4:1;
[0053] S5 enzyme treatment: 55 parts by weight of wood flour and 120 parts by weight of bamboo powder were mixed into 500 parts by weight of water, 2 parts by weight of complex enzyme were added, enzymatic hydrolysis at 50 ℃ for 0.5h, enzyme inactivation, filtration, washing and drying to obtain an enzyme-treated mixed powder;
[0054] The complex enzyme includes hemicellulase and laccase in a mass ratio of 2:7;
[0055] S6. Preparation of environmentally friendly bamboo composite materials: 8 parts by weight of the modified waterborne acrylic resin adhesive prepared in step S4 were added to 10 parts by weight of the enzyme-treated mixed powder prepared in step S5, stirred for 25 min, ultrasonically treated at a power of 700 W for 10 min, hot pressed at a temperature of 145 ° C, a pressure of 5.5 MPa, a time of 10 min, and dried to obtain a bamboo composite material;
[0056] S7. Preparation of environmentally friendly bamboo-wood composite material: The surface of the bamboo-wood composite material obtained in step S6 is coated with a layer of tung oil, the coating amount being 0.03g / cm 2 , dried to obtain an environmentally friendly bamboo-wood composite material.
[0057] Example 2
[0058] This embodiment provides a method for preparing an environmentally friendly bamboo-wood composite material, which specifically comprises the following steps:
[0059] S1. Preparation of N / S doped TiO2 nanopowder: 22 parts by weight of tetrabutyl titanate and 2 parts by weight of thiourea were dissolved in 150 parts by weight of ethanol, 10 parts by weight of water were added dropwise, stirred for 1 hour, centrifuged, washed, dried, and calcined at 700°C for 4 hours to obtain N / S doped TiO2 nanopowder;
[0060] S2. Preparation of tannic acid-modified nanopowder: 20 parts by weight of the N / S-doped TiO2 nanopowder obtained in step S1 was added to 200 parts by weight of water, 7 parts by weight of tannic acid and 12 parts by weight of 2.5 mol / L Tris-HCl buffer were added, the pH value of the solution was adjusted to 8.8, heated to 50°C, stirred for 3h, centrifuged, washed, and dried to obtain tannic acid-modified nanopowder;
[0061] S3. Preparation of modified nanopowder: 22 parts by weight of the tannic acid-modified nanopowder obtained in step S2 was added to 200 parts by weight of water, 5 parts by weight of a silane coupling agent was added, heated to 55 ° C, stirred for 3h, centrifuged, washed, and dried to obtain a modified nanopowder;
[0062] The silane coupling agent is a mixture of KH550 and KH570, with a mass ratio of 4:10;
[0063] S4. Preparation of modified waterborne acrylic resin adhesive: 5 parts by weight of the modified nanopowder obtained in step S3 was added to 150 parts by weight of water, 35 parts by weight of acrylic acid monomer was added, under nitrogen protection, an initiator system was added, heated to 65 ° C, the reaction was stirred for 5h, and part of the solvent was removed under reduced pressure to obtain a modified waterborne acrylic resin adhesive having a relative density of 1.15;
[0064] The acrylic acid monomers include methacrylic acid, 2-hydroxyethyl acrylate, N-hydroxymethyl acrylamide, and methyl acrylate in a mass ratio of 15:10:5:3;
[0065] The initiation system includes potassium persulfate and sodium sulfite in a mass ratio of 6:1;
[0066] S5 enzyme treatment: 60 parts by weight of wood powder and 150 parts by weight of bamboo powder were mixed into 500 parts by weight of water, 4 parts by weight of complex enzyme were added, enzymatic hydrolysis was carried out at 0 ° C for 1h, the enzyme was inactivated, filtered, washed and dried to obtain an enzyme-treated mixed powder;
[0067] The complex enzyme includes hemicellulase and laccase in a mass ratio of 4:9;
[0068] S6. Preparation of environmentally friendly bamboo composite materials: 15 parts by weight of the enzyme-treated mixed powder obtained in step S5 was added 10 parts by weight of the modified waterborne acrylic resin adhesive obtained in step S4, stirred and mixed for 25 min, ultrasonically treated at a power of 1000 W for 15 min, hot pressed at a temperature of 155 ° C, a pressure of 7 MPa, a time of 20 min, and dried to obtain a bamboo composite material;
[0069] S7. Preparation of environmentally friendly bamboo-wood composite material: The surface of the bamboo-wood composite material obtained in step S6 is coated with a layer of tung oil, the coating amount being 0.05g / cm 2 , dried to obtain an environmentally friendly bamboo-wood composite material.
[0070] Example 3
[0071] This embodiment provides a method for preparing an environmentally friendly bamboo-wood composite material, which specifically comprises the following steps:
[0072] S1. Preparation of N / S doped TiO2 nanopowder: 19 parts by weight of tetrabutyl titanate and 1.5 parts by weight of thiourea were dissolved in 135 parts by weight of ethanol, 8 parts by weight of water were added dropwise, stirred for 1 hour, centrifuged, washed, dried, and calcined at 600°C for 3 hours to obtain N / S doped TiO2 nanopowder;
[0073] S2. Preparation of tannic acid-modified nanopowder: 17 parts by weight of the N / S-doped TiO2 nanopowder obtained in step S1 was added to 200 parts by weight of water, 6 parts by weight of tannic acid and 11 parts by weight of 2 mol / L Tris-HCl buffer were added, the pH value of the solution was adjusted to 8.7, heated to 45 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain tannic acid-modified nanopowder;
[0074] S3. Preparation of modified nanopowder: 20 parts by weight of the tannic acid-modified nanopowder obtained in step S2 was added to 200 parts by weight of water, 4 parts by weight of a silane coupling agent was added, heated to 50 ° C, stirred for 2h, centrifuged, washed, and dried to obtain a modified nanopowder;
[0075] The silane coupling agent is a mixture of KH550 and KH570, with a mass ratio of 3:8;
[0076] S4. Preparation of modified waterborne acrylic resin adhesive: 4 parts by weight of the modified nanopowder obtained in step S3 was added to 150 parts by weight of water, 32 parts by weight of acrylic acid monomer was added, under nitrogen protection, an initiator system was added, heated to 60 ° C, the reaction was stirred for 4h, and part of the solvent was removed under reduced pressure to obtain a modified waterborne acrylic resin adhesive having a relative density of 1.12;
[0077] The acrylic acid monomers include methacrylic acid, 2-hydroxyethyl acrylate, N-hydroxymethyl acrylamide, and methyl acrylate in a mass ratio of 13:8:4:2.5;
[0078] The initiation system includes ammonium persulfate and sodium sulfite in a mass ratio of 5:1;
[0079] S5 enzyme treatment: 57 parts by weight of wood powder and 135 parts by weight of bamboo powder were mixed and added to 500 parts by weight of water, 3 parts by weight of complex enzyme was added, enzymatic hydrolysis at 55 ° C for 1h, enzyme inactivation, filtration, washing and drying to obtain an enzyme-treated mixed powder;
[0080] The complex enzyme includes hemicellulase and laccase in a mass ratio of 3:8;
[0081] S6. Preparation of environmentally friendly bamboo composite materials: 12 parts by weight of the enzyme-treated mixed powder obtained in step S5 was added 9 parts by weight of the modified waterborne acrylic resin adhesive obtained in step S4, stirred and mixed for 25 min, ultrasonically treated at a power of 850 W for 12 min, hot pressed at a temperature of 150 ° C, a pressure of 6.6 MPa, a time of 15 min, and dried to obtain a bamboo composite material;
[0082] S7. Preparation of environmentally friendly bamboo-wood composite material: The surface of the bamboo-wood composite material obtained in step S6 is coated with a layer of tung oil, the coating amount being 0.04g / cm 2 , dried to obtain an environmentally friendly bamboo-wood composite material.
[0083] Comparative Example 1
[0084] Compared with Example 3, the difference is that the silane coupling agent is a single KH550.
[0085] Comparative Example 2
[0086] Compared with Example 3, the difference is that the silane coupling agent is a single KH570.
[0087] Comparative Example 3
[0088] Compared with Example 3, the difference is that the complex enzyme is a single hemicellulase.
[0089] Comparative Example 4
[0090] Compared with Example 3, the difference is that the composite enzyme is a single laccase.
[0091] Comparative Example 5
[0092] Compared with Example 3, the difference is that thiourea in step S1 is replaced by urea in an equal molar amount.
[0093] Comparative Example 6
[0094] Compared with Example 3, the difference is that thiourea is not added in step S1.
[0095] Comparative Example 7
[0096] Compared with Example 3, the difference is that step S2 is not performed.
[0097] Comparative Example 8
[0098] Compared with Example 3, the difference is that step S3 is not performed.
[0099] Comparative Example 9
[0100] Compared with Embodiment 3, the difference is that step S5 is not performed.
[0101] Comparative Example 10
[0102] Compared with Example 3, the difference is that no ultrasonic treatment is performed in step S6.
[0103] Comparative Example 11
[0104] Compared with the embodiment 3, the difference is that step S7 is not performed.
[0105] Test Example 1
[0106] The environmentally friendly bamboo-wood composite materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-11 were subjected to performance tests.
[0107] Mechanical properties test: The mechanical properties of the material are tested according to GB / T 4897-2015.
[0108] Odor test: A team of 20 professionals will evaluate the odor of the above materials. Odor evaluation level: Level 1: no odor; Level 2: slight odor; Level 3: odor, but not irritating; Level 4: irritating odor, or irritating odor, but strong; Level 5: strong irritating odor; Level 6: unbearable odor.
[0109] Limiting Oxygen Index (LOI): According to the national standard GB / T 2406.2-2009, the test sample size is 100.0mm×10.0mm×4.0mm.
[0110] The results are shown in Table 1.
[0111] Table 1
[0112]
[0113] It can be seen from the above table that the environmentally friendly bamboo-wood composite materials prepared in Examples 1-3 of the present invention have good mechanical properties, good internal bonding strength, certain flame retardant properties, almost no odor, and certain waterproof properties.
[0114] Test Example 2
[0115] The antibacterial and anti-mildew properties of the lightweight bamboo-wood composite materials prepared in Examples 1-3 and Comparative Examples 1-11 were tested according to JC / T 2039-2010. The results are shown in Table 2.
[0116] Table 2
[0117]
[0118] It can be seen from the above table that the environmentally friendly bamboo-wood composite materials prepared in Examples 1-3 of the present invention have good antibacterial and anti-mildew properties.
[0119] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an environmentally friendly bamboo-wood composite material, characterized in that: The following steps are involved: S1. Preparation of N / S doped TiO2 nanopowder: dissolve tetrabutyl titanate and thiourea in ethanol, add water dropwise, stir to react, centrifuge, wash, dry, and calcine to obtain N / S doped TiO2 nanopowder; the mass ratio of tetrabutyl titanate, thiourea, ethanol, and water is 15-22:1-2:120-150:7-10; the stirring reaction time is 0.5-1h, the calcination temperature is 500-700°C, and the time is 2-4h; S2. Preparation of tannic acid-modified nanopowder: The N / S-doped TiO2 nanopowder obtained in step S1 was added to water, tannic acid and Tris-HCl buffer were added, the pH value of the solution was adjusted, the reaction was heated and stirred, centrifuged, washed, and dried to obtain tannic acid-modified nanopowder; S3. Preparation of modified nanopowder: adding the tannic acid modified nanopowder obtained in step S2 to water, adding a silane coupling agent, heating and stirring the reaction, centrifuging, washing, and drying to obtain a modified nanopowder; the silane coupling agent is a mixture of KH550 and KH570 in a mass ratio of 2-4:7-10; the mass ratio of the tannic acid modified nanopowder to the silane coupling agent is 17-22:3-5, the heating and stirring reaction temperature is 45-55°C, and the time is 1-3h; S4 modified water-based acrylic resin adhesive preparation: the modified nanopowder obtained in step S3 was added to water, an acrylic monomer was added, under inert gas protection, an initiator system was added, the reaction was heated and stirred, and part of the solvent was removed under reduced pressure to obtain a modified water-based acrylic resin adhesive; S5. Enzyme treatment: mixing wood powder and bamboo powder into water, adding composite enzyme, enzymolysis, inactivating enzyme, filtering, washing, drying, and obtaining enzyme-treated mixed powder; the composite enzyme comprises hemicellulase and laccase in a mass ratio of 2-4:7-9; the mass ratio of wood powder, bamboo powder and composite enzyme is 55-60:120-150:2-4, the enzymolysis temperature is 50-60°C, and the time is 0.5-1h; S6 environmentally friendly bamboo composite material preparation: the enzyme treatment of step S5 prepared by adding the modified waterborne acrylic resin adhesive prepared in step S4, mixed, ultrasonic treatment, hot pressing, drying, to obtain a bamboo composite material; S7. Preparation of an environmentally friendly bamboo-wood composite material: coating the surface of the bamboo-wood composite material obtained in step S6 with a layer of tung oil and drying the surface to obtain an environmentally friendly bamboo-wood composite material.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the N / S-doped TiO2 nanopowder, tannic acid and Tris-HCl buffer in step S2 is 15-20:5-7:10-12, the Tris-HCl buffer is 1.5-2.5 mol / L Tris-HCl buffer, the amount of Tris-HCl buffer added is such that the pH value of the system is 8.5-8.8, the temperature of the heated and stirred reaction is 40-50°C, and the time is 1-3h.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the modified nanopowder and the acrylic monomer in step S4 is 3-5:30-35, the acrylic monomer includes methacrylic acid, 2-hydroxyethyl acrylate, N-hydroxymethyl acrylamide, and methyl acrylate, and the mass ratio is 12-15:7-10:3-5:2-3, the initiator system includes an initiator and a co-initiator, and the mass ratio is 4-6:1, the initiator is at least one of sodium persulfate, potassium persulfate, and ammonium persulfate, and the co-initiator is sodium sulfite. The addition of the initiator system is 0.5-1wt% of the total mass of the system, the temperature of the heating and stirring reaction is 55-65°C, the time is 3-5h, and the relative density of the modified water-based acrylic resin adhesive is 1.1-1.
15.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the enzyme-treated mixed powder and the modified water-based acrylic resin adhesive in step S6 is 10-15:8-10, the temperature of the hot pressing molding is 145-155°C, the pressure is 5.5-7Mpa, the time is 10-20min, the power of the ultrasonic treatment is 700-1000W, and the time is 10-15min; the coating amount of tung oil in step S7 is 0.03-0.05g / cm 2 .
5. The preparation method according to claim 1, characterized in that: The specific steps include: S1. Preparation of N / S doped TiO2 nanopowder: 15-22 parts by weight of tetrabutyl titanate and 1-2 parts by weight of thiourea are dissolved in 120-150 parts by weight of ethanol, 7-10 parts by weight of water are added dropwise, the reaction is stirred for 0.5-1h, centrifuged, washed, dried, and calcined at 500-700°C for 2-4h to obtain N / S doped TiO2 nanopowder; S2. Preparation of tannic acid modified nanopowder: 15-20 parts by weight of the N / S doped TiO2 nanopowder obtained in step S1 was added to 200 parts by weight of water, 5-7 parts by weight of tannic acid and 10-12 parts by weight of 1.5-2.5 mol / L Tris-HCl buffer were added, the pH value of the solution was adjusted to 8.5-8.8, heated to 40-50 ° C, stirred for 1-3h, centrifuged, washed, and dried to obtain tannic acid modified nanopowder; S3. Preparation of modified nanopowder: 17-22 parts by weight of the tannic acid modified nanopowder obtained in step S2 was added to 200 parts by weight of water, 3-5 parts by weight of a silane coupling agent was added, heated to 45-55 ° C, stirred for 1-3h, centrifuged, washed, and dried to obtain a modified nanopowder; The silane coupling agent is a mixture of KH550 and KH570, with a mass ratio of 2-4:7-10; S4. Preparation of a modified waterborne acrylic resin adhesive: 3-5 parts by weight of the modified nanopowder obtained in step S3 was added to 150 parts by weight of water, 30-35 parts by weight of an acrylic monomer was added, under inert gas protection, an initiator system was added, heated to 55-65 ° C, the reaction was stirred for 3-5h, and part of the solvent was removed under reduced pressure to obtain a modified waterborne acrylic resin adhesive having a relative density of 1.1-1.15; The acrylic acid monomers include methacrylic acid, 2-hydroxyethyl acrylate, N-hydroxymethyl acrylamide, and methyl acrylate in a mass ratio of 12-15:7-10:3-5:2-3; The initiation system comprises an initiator and sodium sulfite in a mass ratio of 4-6:1; S5 enzyme treatment: 55-60 parts by weight of wood flour and 120-150 parts by weight of bamboo powder were mixed and added to 500 parts by weight of water, 2-4 parts by weight of complex enzyme was added, enzymatic hydrolysis was carried out at 50-60 ℃ for 0.5-1h, the enzyme was inactivated, filtered, washed and dried to obtain an enzyme-treated mixed powder; The complex enzyme includes hemicellulase and laccase in a mass ratio of 2-4:7-9; S6. Preparation of environmentally friendly bamboo composite materials: 8-10 parts by weight of the modified waterborne acrylic resin adhesive prepared in step S4 was added to 10-15 parts by weight of the enzyme-treated mixed powder prepared in step S5, mixed evenly, ultrasonically treated at a power of 700-1000W for 10-15min, hot-pressed at a temperature of 145-155°C, a pressure of 5.5-7Mpa, for 10-20min, and dried to obtain a bamboo composite material; S7. Preparation of environmentally friendly bamboo-wood composite material: The surface of the bamboo-wood composite material obtained in step S6 is coated with a layer of tung oil, the coating amount being 0.03-0.05g / cm 2 , dried to obtain an environmentally friendly bamboo-wood composite material.
6. An environmentally friendly bamboo-wood composite material obtained by the preparation method according to any one of claims 1 to 5.
Citation Information
Patent Citations
A lightweight bamboo-wood composite material and preparation method thereof
CN118493546B
Formaldehyde-removing interior wall latex paint with visible light catalytic property and preparation method of interior wall latex paint
CN103205151A
Antibacterial flame-retardant plastic, preparation method thereof and food bottle prepared from antibacterial flame-retardant plastic
CN117362834A
Flame-retardant heat-resistant bamboo-wood composite board and preparation method thereof
CN118123961A
High-strength bamboo-wood composite material and preparation method thereof
CN118325355A